2015
DOI: 10.1007/s13197-015-1734-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the combination of natural antioxidants and packaging methods on quality of pork patties during storage

Abstract: The effect of combination of phyto-extracts (sea buckthorn extract (SBTE), grape seed extract (GSE)) on different physico-chemical, oxidative stability, instrumental colour and texture, sensory and microbiological properties of pork patties were investigated under aerobic and MAP (50 % CO2: 50 % N2) packaging conditions. Treatments viz. T-1 (aerobic packaged control), T-2 (aerobic packaged containing 0.3 % SBTE+ 0.1 % GSE), T-3 (MAP packaged control) and T-4 (MAP packaged containing 0.3 % SBTE+ 0.1 % GSE) at 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 55 publications
10
31
0
Order By: Relevance
“…It was lower ( p < 0.05) in WMRE incorporated patties than controls. On the last day of storage, lowest count was noted in T and highest in C. Similar trends have also been reported by Kumar et al () in pork patties incorporated with phyto‐extracts. The better microbial quality of treated products as compared to control could be due to antibacterial activity of phenolic compounds in WMRE.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…It was lower ( p < 0.05) in WMRE incorporated patties than controls. On the last day of storage, lowest count was noted in T and highest in C. Similar trends have also been reported by Kumar et al () in pork patties incorporated with phyto‐extracts. The better microbial quality of treated products as compared to control could be due to antibacterial activity of phenolic compounds in WMRE.…”
Section: Resultssupporting
confidence: 88%
“…Incorporation of WMRE had resulted in significantly lower (p < 0.05) microbial count in treated patties during refrigerated aerobic storage as compared to PC and C ( Kumar et al (2015) in pork patties incorporated with phyto-extracts. The better microbial quality of treated products as compared to control could be due to antibacterial activity of phenolic compounds in WMRE.…”
Section: Microbial Qualitymentioning
confidence: 94%
See 1 more Smart Citation
“…Vacuum packaging increase the self-life of product which might be due to the absence of the O 2 in vacuum packaged product which is considered as chelating agent for lipid oxidation (Ahn et al, 1998). Similar result was found by Kumar et al, (2015) in pork patties added with combination of natural antioxidants using combination of packaging methods.…”
Section: Free Fatty Acidsupporting
confidence: 61%
“…Similar results have recently been pointed out by Hasani and Alizadeh (), however, in this case, the effect was less relevant than in other studies. Other researchers showed that low concentrations of grape extracts (lower than 0.2%) had no effect on the final population or only produced slightly lower final counts of TAMB (Garrido and others ; Kumar and others ). The lack of any antimicrobial effect was ascribed to the low level applied and to matrix–phenol interactions that may limit the antimicrobial capacity of phenolic compounds.…”
Section: Functions In the Food Industrymentioning
confidence: 96%